In vitro modelling of respiratory infections in idiopathic pulmonary fibrosis (IPF) using human induced pluripotent stem cell (hiPSCs)-derived alveolar epithelial type II cells - Serna Valverde, Ana Lilia (2023)
Idiopathic pulmonary fibrosis (IPF) is a chronic, interstitial lung disease estimated to affect 4.5 individuals per 10,000[1]. It is characterised by the accumulation of extracellular matrix in the lung interstitium, which disrupts the normal architecture and impairs lung function resulting in severe respiratory failure and death. The rapid progression of IPF and the lack of curative treatments is often accompanied by a median survival of 2-3 years [2]. Its aetiology is unclear; however, environmental and genetic risk factors indicate that alveolar epithelial type 2 cells (AT2s), the facultative progenitor of the alveoli, play a pivotal role [3, 4]. Mutations in surfactant protein (SFTPC) genes compromise AT2s function and viability, reducing its capacity to regenerate damaged alveolar epithelial tissue. This function is further compromised by infection-induced lung injury. Integrating such environmental stimuli and genetic predisposition in IPF patients results in an aberrant fibrotic response driven by AT2s [5, 6].